Non-benevolent central banks - Johann Lambsdorff; Michael Schinke (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2002)
Corruption at central banks induces distorted policies by generating a tendency to increase inflation. An inflation bias arises because the public distrusts central bank's benevolence, not only its commitments. We show that distrust among the public, measured by a high level of expected inflation, can have positive effects because it may sanction a conservative central banker, forcing him to lower realized inflation levels. Giving central banks a high level of independence will fail if this not only insulates central bankers from troublesome political interference but also provides them with the leeway necessary to carry out corrupt transactions.
Keywords: E5; K42; 330; Corruption; central banks; time-inconsistency; inflation bias; seignorage; central bank independence